2006
DOI: 10.1124/jpet.106.109322
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Regulation of Ether-a-go-go-Related Gene K+ Currents in Interstitial Cells of Cajal

Abstract: The interstitial cells of Cajal (ICC) of the myenteric plexus generate a set of currents that evoke a pacemaker potential that sets the initial conditions for the contraction frequency and duration of the electrically coupled intestinal musculature. The synapse-like contacts between ICC and myenteric motor nerves highlight the potential role of the enteric nervous system in regulating the pacemaking currents in ICC. The objective of the present study was to investigate muscarinic regulation of the ether-a-go-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…mouse ERG currents (McKay and Huizinga, 2006;Yeung and Greenwood, 2007). In general, ERG1b and ERG3 deactivate much faster than ERG1a and ERG2 (Lees-Miller et al, 1997;Hirdes et al, 2005), and there are significant species variations in deact (Tseng, 2001).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…mouse ERG currents (McKay and Huizinga, 2006;Yeung and Greenwood, 2007). In general, ERG1b and ERG3 deactivate much faster than ERG1a and ERG2 (Lees-Miller et al, 1997;Hirdes et al, 2005), and there are significant species variations in deact (Tseng, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…During depolarization, we observed a substantial E-4031-sensitive steady-state outward current, likely attributable to activation of ERG3. This subunit shows fast activation kinetics and slow steady-state inactivation (Shi et al, 1997;McKay and Huizinga, 2006), resulting in weak inward rectification (Wimmers et al, 2002). Eleven of 27 neurons showed no drug-sensitive current (Fig.…”
Section: Biophysical "Fingerprint" Of Vomeronasal Erg Channels: Currementioning
confidence: 99%
“…The acute effects of PKC activation have been examined in several different experimental systems, using either activators of PKC such as diacylglycerol (DAG)/l-oleoyl-2-acetylsn-glycerol (OAG) and phorbol 12-myristate 13-acetate (PMA) (53, 113,633) or by studying G protein-coupled receptors linked to PKC activation, including TRH receptor (213), angiotensin II receptor AT1 (676), ␣-adrenoceptors (631,671), and muscarinic receptors (113,260,407). Acute activation of PKC typically results in reduced KV11.1 current in oocytes (53, 630, 633) and HEK293 cells (113,513,676), as well as isolated guinea pig ventricular myocytes (671).…”
Section: Pkcmentioning
confidence: 99%
“…ICC express receptors for neurotransmitters such as neurokinins (NK1 and NK3 receptors), vasoactive intestinal polypeptide (VIP-1 receptors) and acetylcholine (muscarinic M 2 and M 3 receptors). 62,127,[191][192][193][194][195][196][197] Numerous studies have shown responses to NO in the GI tract depend upon the production of cyclic GMP (cGMP) by soluble guanylate cyclase. [198][199][200] Guanylate cyclase is a heterodimer comprised of 2 subunits, α and β.…”
Section: Functional Evidence Demonstrating the Importance Of Interstimentioning
confidence: 99%